Colossal positive and negative thermal expansion in the framework material Ag3[Co(CN)6]. - Goodwin, A; Calleja, M; Conterio, M; Dove, M; Evans, J; Keen, D; Peters, L; Tucker, MG (2008)
We show that silver(I) hexacyanocobaltate(III), Ag3[Co(CN)6], exhibits positive and negative thermal expansion an order of magnitude greater than that seen in other crystalline materials. This framework material expands along one set of directions at a rate comparable to the most weakly bound solids known. By flexing like lattice fencing, the framework couples this to a contraction along a perpendicular direction. This gives negative thermal expansion that is 14 times larger than in ZrW2O8. Density functional theory calculations quantify both the low energy associated with this flexibility and the role of argentophilic (Ag+...Ag+) interactions. This study illustrates how the mechanical properties of a van der Waals solid might be engineered into a rigid, useable framework.